Effects of source sample amount on biodiversity surveys of bacteria, fungi, and nematodes in soil ecosystems - Kageyama, Takuya; Toju, Hirokazu (Frontiers in Ecology and Evolution, 2022)
Bacteria, fungi, and nematodes are major components of soil ecosystems, playing pivotal roles in belowground material cycles and biological community processes. A number of studies have recently uncovered the diversity and community structure of those organisms in various types of soil ecosystems based on DNA metabarcoding (amplicon sequencing). However, because most previous studies examined only one or two of the three organismal groups, it remains an important challenge to reveal the entire picture of soil community structure. We examined how we could standardize DNA extraction protocols for simultaneous DNA metabarcoding of bacteria, fungi, and nematodes. Specifically, in an Illumina sequencing analysis of forest and farmland soil samples, we performed DNA extraction at five levels of soil-amount (0.5, 2, 5, 10, and 20 g). We then found that DNA extraction with the 0.5 g soil setting, which had been applied as default in many commercial DNA extraction kits, could lead to underestimation of α-diversity in nematode community. We also found that dissimilarity (β-diversity) estimates of community structure among replicate samples could be affected by soil sample amount. Based on the assays, we conclude that DNA extraction from at least 20 g of soil is a standard for comparing biodiversity patterns among bacteria, fungi and nematodes.